Kebijakan Luar Negeri Obama Dalam Konflik Timur Tengah - Laode Muhamad Fathun (Jurnal ICMES, 2017)
The ex-US President, Barack Obama, was the first black-president, prompting hopes that he would make a more humanist foreign policy in the United States. Obama comes from the Democratic Party which is aggressively promoting democracy, humanism, and human rights. But in reality, during the two periods of Obama administration, the United States continues to wage war against the Middle East countries, whether directly or indirectly. This article raises the question, what shaped US foreign policy in the Middle East during the Obama administration. To answer the question the writer uses the wholistic and rational actor theory. The finding of this article is that wholistically, Obama does have characteristic differences, but the foreign policy he decided was the same as his predecessor presidents, prioritizing US-political economic interests in the region rather than keeping peace.